Exploration of Dietetics Graduate Students’ Experience in a Flipped Course Using Learning Reflections - Vollmer, Rachel L.; Drake, Teresa (Journal of nutrition education and behavior, 2020)
Evaluate graduate students’ experience in a flipped metabolism course using periodic learning reflections. Two cohorts of graduate students (n = 17, total) were recruited from an advanced metabolism course using a flipped learning approach during the fall 2016 and 2017 semesters. After course completion, 2 investigators used content analysis to develop themes from 8 structured learning reflections. Four themes were developed from the reflections: responsibility for learning, metacognition, team-based learning, and transfer of skills. Resistance to flipped learning peaked at week 4 of the semester. By the end of the semester, students seemed to embrace the flipped approach and self-directed learning. Despite reporting being better self-directed learners by the end of the semester, students may struggle with the flipped learning format early in the semester. Thus, instructors may need to adopt supportive techniques with students initially.